Precise GNSS-acoustic seafloor positioning with sound speed from global ocean analysis - Yang Liu; Tianjie Shi; Yanxiong Liu; Shengli Wang; Guanxu Chen; Menghao Li; Qiuhua Tang; Yikai Feng (Satellite Navigation)
Abstract The Global Navigation Satellite System–Acoustic (GNSS-A) combined positioning technique extends geodetic networks into the seafloor. Currently, GNSS-A can achieve static seafloor positioning accuracy at centimeter level. However, in practical operations, substantial time, manpower, financial and instrument resources are required to measure in situ Sound Speed Profiles (SSPs). This paper evaluates the feasibility of GNSS-A with alternative SSPs instead of in situ measurements. The GNSS-A positioning using three different SSPs are compared: the Munk empirical profile, the profiles from the HYbrid Coordinate Ocean Model (HYCOM) global ocean analysis product, and the in situ profiles. Compared with the in situ profile, the Munk SSP has little impact on the GNSS-A horizontal position (0.6 cm in root-mean-square, RMS) but introduces a large systematic error in the vertical position (10.3 cm in RMS), and the impact on the displacement velocity is at the mm/a level. When the HYCOM profile is substituted for in situ profiles, the impact on GNSS-A positioning is only 0.2 cm in the horizontal and 2.9 cm in the vertical, and the impact on displacement velocity is at the sub-mm/a level in the horizontal and mm/a level in the vertical. The HYCOM global ocean analysis SSPs can largely serve as a cost-effective substitute for in situ profiles in GNSS-A seafloor positioning, which is especially applicable to GNSS-A measurements using unmanned surface vehicles, for which full-depth SSP measurements are difficult. Therefore, when SSPs are selected, appropriate decisions should be made on the basis of specific GNSS-A application needs and conditions.